The CAP, its Challenges and the European Green Deal - Haniotis, Tassos (2020)
Tassos Haniotis POLICY SEMINAR European Green Deal -- Farm to Fork Strategy for Sustainable Food Co-Organized by IFPRI and the European Union FEB 18, 2020 - 12:15 PM TO 01:30 PM EST